Indonesian Football 1951-1967: The Golden Age? - Budi Harjo Sayoga; Didik Pradjoko; Agus Setiawan (International Journal Labs, 2025)
The background of this study departs from the phenomenon that, although Indonesia has not made significant global achievements, the period is considered the peak of the national team's accomplishments at the Asian and world levels. This study discusses the journey of Indonesian football during the period 1951–1967, a period often referred to as the